การประเมินประสิทธิผลศูนย์เรียนรู้พลังงานชุมชน / Evaluation of the Effectiveness of Community Energy Learning Centers - Thanongkij, Rujira; Poboon, Chamlong (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
ศูนย์เรียนรู้พลังงานชุมชนซึ่งตั้งอยู่ใน 4 ภูมิภาคของประเทศไทย เกิดขึ้นโดยการส่งเสริมสนับสนุนของส่วนพลังงานชุมชน ฝ่ายกิจการเพื่อสังคม บริษัท ปตท.จำกัด (มหาชน) เพื่อช่วยขับเคลื่อนให้เกิดความมั่นคงทางด้านพลังงานในระดับชุมชน การศึกษาครั้งนี้มีวัตถุประสงค์ เพื่อ 1) ศึกษาผลการดำเนินงานศูนย์เรียนรู้พลังงานชุมชน 2) ศึกษาปัจจัยที่ส่งผลต่อการดำเนินงานและผลสำเร็จของศูนย์เรียนรู้พลังงานชุมชน ใช้กรอบแนวการศึกษา CIPP Model เก็บรวบรวมข้อมูลโดยใช้แบบสอบถามกับคณะกรรมการศูนย์เรียนรู้พลังงานชุมชนทั้ง 4 แห่ง ใน 4 ภูมิภาค จำนวน 78 คน (ร้อยละ 100) ผลการวิเคราะห์ค่าสหสัมพันธ์แบบเพียร์สัน พบว่า การดำเนินงานศูนย์เรียนรู้ในภาพรวม พบว่า ปัจจัยภายนอก ปัจจัยนำเข้า และกระบวนการ มีความสัมพันธ์กับประสิทธิผลในระดับสูง ที่ระดับนัยสำคัญทางสถิติ 0.01 สามารถจำแนกเป็นรายภาคได้ ดังนี้ ศูนย์เรียนรู้พลังงานชุมชนภาคเหนือ พบว่า ปัจจัยนำเข้าและกระบวนการ มีความสัมพันธ์กับประสิทธิผลในระดับสูง ที่ระดับนัยสำคัญทางสถิติ 0.01 ส่วนปัจจัยภายนอกมีความสัมพันธ์กับประสิทธิผลในระดับปานกลาง ที่ระดับนัยสำคัญทางสถิติ 0.05 ศูนย์เรียนรู้พลังงานชุมชนภาคกลาง พบว่า ปัจจัยภายนอก ปัจจัยนำเข้า และกระบวนการไม่มีความสัมพันธ์กับประสิทธิผลศูนย์เรียนรู้พลังงานชุมชนภาคตะวันออกเฉียงเหนือ พบว่า ปัจจัยภายนอก ปัจจัยนำเข้า และกระบวนการ มีความสัมพันธ์กับประสิทธิผลในระดับสูง ที่ระดับนัยสำคัญทางสถิติ 0.01 และศูนย์เรียนรู้พลังงานชุมชนภาคใต้ พบว่า ปัจจัยภายนอก มีความสัมพันธ์กับประสิทธิผลในระดับสูง ที่ระดับนัยสำคัญทางสถิติ 0.01 กระบวนการมีความสัมพันธ์กับประสิทธิผลในระดับปานกลาง ที่ระดับนัยสำคัญทางสถิติ 0.05 และปัจจัยนำเข้าไม่มีความสัมพันธ์กับประสิทธิผล      ข้อเสนอแนะเพื่อการดำเนินงานศูนย์เรียนรู้พลังงานชุมชนให้ยั่งยืน ได้แก่ ด้านปัจจัยภายนอก ควรมีนโยบายด้านพลังงานทดแทนที่สอดคล้องกับฐานทรัพยากรชุมชน มีพื้นที่ให้แลกเปลี่ยนความรู้ และมีการเผยแพร่องค์ความรู้สู่สาธารณะอย่างต่อเนื่อง ด้านปัจจัยนำเข้า ควรสร้างความเชื่อมั่น การรับรู้ การตระหนักรู้และความชำนาญทางด้านเทคโนโลยีพลังงานชุมชนแก่ชุมชน ด้านกระบวนการ ควรพิจารณาแผนการทำงานของชุมชนเป็นหลักในการสนับสนุน และมีการบูรณาการการทำงานร่วมกัน      The community energy learning centers located in 4 regions of Thailand were initiated and supported by the Community Energy Division, Social Enterprise Department of PTT Public Company Limited, in order to build up energy security in local communities. The objectives of this research were 1) to study the performance of the 4 community energy learning centers focused on in the study, and 2) to study the factors influencing the performance and achievement of these community energy learning centers. The CIPP Model was employed as a conceptual framework for this study. Data were collected by distributing questionnaires to all 78 members (100%) of the committees of the 4 centers. By using Pearson correlation analysis, it was found that context, input, and process had a high relation with effectiveness at the statistical significance of 0.01. For the northern center it was found that input and process had a high relation with effectiveness at the statistical significance of 0.01, but context had only a moderate relation with effectiveness at the statistical significance of 0.05. For the central center, context, input, and process did not have a relation with effectiveness. For the northeast center, context, input, and process had a high relation with effectiveness at the statistical significance of 0.01. For the southern center, context had a high relation with effectiveness at the statistical significance of 0.01, while process had a moderate relation with effectiveness at the statistical significance of 0.05, and input had no relation with effectiveness.      Suggestions for the sustainable operation of community energy learning centers are, regarding context, that the centers should implement renewable energy policy that is consistent with community’s resource base; they should provide opportunities for knowledge exchange and continuous dissemination of information to the public; regarding input, the center should cultivate confidence, perception, recognition, and expertise in the community’s energy technology for the communities; in terms of process, the centers should mainly focus their support on the community’s plans, as well as integrate their operations with the communities.
Keywords: Effectiveness Energy Community Learning Center, Community’s Energy